(untitled) (Journal of the Digital Humanities Association of Southern Africa (DHASA), 2023)
Psycholinguistic research on isiXhosa and related Bantu languages is scarce. For research on lexical processing in particular, a prerequisite is data on lexical properties that impact word recognition, such as word frequency and neighbourhood density. This paper describes the derivation of these and related lexical statistics from a newly created 4.8-million-word isiXhosa corpus. It then reviews the potential applications of such a lexical database for research on language acquisition, language development, and language processing. The paper closes with recommendations for further work in this domain.